Elements of Al- Ghaflah In Relations to Online Game Addiction In Relations to Al-Ghaflah (Heedlessness); A Case Study on University Students - Azizah Abdul Majid; Nur Safura Ab. Ghaffar; Mohammed Akhiruddin Ibrahim; Raimizar Rahim (Academic Inspired Network (AIN), 2024)
Non-Indexed Publication